2018
DOI: 10.1111/dgd.12421
|View full text |Cite
|
Sign up to set email alerts
|

Nanos3 of the frog Rana rugosa: Molecular cloning and characterization

Abstract: Nanos is expressed in the primordial germ cells (PGCs) and also the germ cells of a variety of organisms as diverse as Drosophila, medaka fish, Xenopus and mouse. In Nanos3-deficient mice, PGCs fail to incorporate into the gonad and the size of the testis and ovary is thereby dramatically reduced. To elucidate the role of Nanos in an amphibian species, we cloned Nanos3 cDNA from the testis of the R. rugosa frog. RT-PCR analysis showed strong expression of Nanos3 mRNA in the testis of adult R. rugosa frogs, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Previously we have shown that the W - AR is hardly expressed in R . rugosa embryos compared with Z-AR [10]. We then hypothesized that Z - AR came to play a role, perhaps a critical one given its sex hormone-signaling function, in male sex determination in ZZ/ZW R .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously we have shown that the W - AR is hardly expressed in R . rugosa embryos compared with Z-AR [10]. We then hypothesized that Z - AR came to play a role, perhaps a critical one given its sex hormone-signaling function, in male sex determination in ZZ/ZW R .…”
Section: Discussionmentioning
confidence: 99%
“…Tg and pTg embryos and tadpoles were reared as previously described [3]. To confirm Z-AR integration into genomic DNA, we extracted DNA from the tail tip of all Tg tadpoles at St. V, using the AllPrep DNA/RNA Micro Kit (QIAGEN, Tokyo, Japan) [10]. The PCR primers used were: forward, and reverse, .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations